2020
DOI: 10.1007/s40266-020-00808-4
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Talk between Age, Hypertension and Inflammation in COVID-19 Patients: Therapeutic Targets

Abstract: This paper presents a brief overview of the complex interaction between age, hypertension, the renin–angiotensin–aldosterone system (RAAS), inflammation, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection. Coronavirus disease 2019 (COVID-19) is more frequent and more severe in comorbid elderly patients, especially those with hypertension, diabetes, obesity, or cardiovascular diseases. There are concerns regarding the use of RAAS inhibitors in patients with COVID-19. Some physicians have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
(65 reference statements)
1
11
0
3
Order By: Relevance
“…K-M analyze, univariate and multivariate Cox hazard analysis in the total patients con rmed that hypertension is the most independent risk factor of developing adverse clinical outcome in elderly COVID-19 patients, which consistent with previous research (14,15). The pathophysiologic mechanisms are generally believed to be the following two aspects: a critical interaction between SARS-CoV-2 and the angiotensin-converting enzyme 2(ACE2) (16, 17); the hypotension medicines which act on ACE2 (18,19).…”
Section: Discussionsupporting
confidence: 89%
“…K-M analyze, univariate and multivariate Cox hazard analysis in the total patients con rmed that hypertension is the most independent risk factor of developing adverse clinical outcome in elderly COVID-19 patients, which consistent with previous research (14,15). The pathophysiologic mechanisms are generally believed to be the following two aspects: a critical interaction between SARS-CoV-2 and the angiotensin-converting enzyme 2(ACE2) (16, 17); the hypotension medicines which act on ACE2 (18,19).…”
Section: Discussionsupporting
confidence: 89%
“…ACE2 is a key enzyme that regulates the renin-angiotensin system associated with hypertension. Therefore, the crosstalk between hypertension and COVID-19 is mediated by the renin-angiotensin system [ 29 , 72 ]. Our analysis also found that the renin-angiotensin system is shared by hypertension and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment’s efficacy could be increased if the molecular pathway crosstalk between the specific comorbidity and COVID-19 is understood and that crosstalk-based targets and targeting drugs are used towards personalized medication. Although, some reports are available such as crosstalk between COVID-19 and breast cancer [ 24 , 25 ], COVID-19 and Alzheimer’s disease [ 26 ], COVID-19 and ischemic stroke [ 27 ], hyperthyroidism and COVID-19 [ 28 ], COVID-19 and age, and COVID-19 and hypertension [ 29 ]; omics-based molecular pathway crosstalk between COVID-19 and its associated vital comorbid conditions and those crosstalk-based targets have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the interaction between inhaled corticoids, ACE-2 antagonists and statins and Covid-19 is most probably mediated by their effect as inflammatory modulators, at the local level in alveolar epithelia (ACE-2 inhibitors and inhaled corticoids) or systemically (statins). Given that ageing is related to a more pro-inflammatory status ( Casucci et al, 2020 ) our observations may not be easily translated to the general population. Furthermore, the protective effect of these drugs could be due to long-term intake having caused chronic changes in the tissues targeted (i.e.…”
Section: Discussionmentioning
confidence: 95%